Implicit measure of suicidal ideation in patients with depression. Issue 8 (14th September 2022) - Wang, Xu; Lei, Wei; Liu, Kezhi; Liang, Xuemei; Wang, Yan; Huang, Chaohua; Zhang, Tao; Chen, Jing
Abstract: The death/suicide implicit association test (IAT) may be more resilient to accurately assess suicide risk than self-reports. We examined the IAT in 130 patients with depression and 125 healthy controls, along with self-reported suicidal ideation. IAT could differentiate patients with suicide attempts from patients without suicide attempts and controls. IAT measures were significantly correlated to explicit suicidal ideation and clinical symptoms in patients. Moreover, the IAT-symptom correlations were significant in female but not male patients. The IAT showed promise as a valid tool to estimate suicide risk in patients with depression and may be particularly useful in female patients.